Marketing político e racionalidade tecnológica: um estudo psicossocial - Gonçalves Júnior, Gil (2008)
The subject in study in this research is political marketing, especially when it happens through election campaigns. Considering that the marketing intuit, when we talk about politics, or about economic relations, is to mobilize psychic matters presents in the wishes of their addressee, taking them into decisions which are not necessarily rational, having a psycho technical function, the possible success in the political marketing denies the identity implied in the mechanism of power delegations through the straight and free vote of the citizens. This way, the political marketing is a matter of interest of the social psychology, area in which this work is inserted and, the way it may affect an important basis of democracy: power delegation through straight and free vote of the citizens, also consists in a theme with scientific and social interest, what justifies its study. This study starts analyzing the way political marketing is introduced into written material by professionals of the area and studiouses of the theme, through it was possible to observe the presence of rational technology into and in consequence of the political marketing. After that, recurring to sayings of critical theorists of the society, this connection between political marketing and technological rationality is analyzed in details, in a way to explicit the historical and economical determinations of such connection, as well as delimitate more precisely its psychosocial dimension. Finally, with basis into the previous reflections and conclusions, it was analyzed a publicity election key diffused by the television. As a result of this set of procedures, it was verified that political marketing, as well as its simile applied to economical relations, is constituted into the factor of technological rationality and, this way, is configured as a suitable practice with the reduction of democracy to its mechanisms, determined by this same rationality, once your action presupposes and reaffirms two aspects of this reduction: the shutting of the political universe and the obstruction of the constitution of the implied individuality to the mechanism of delegation through the power of the vote